Eliminating ambiguities for quantum corrections to strings moving in AdS4×CP3 - Lopez-Arcos, Cristhiam [UNESP]; Nastase, Horatiu [UNESP] (World Scientific Publishing, 2013)
We apply a physical principle, previously used to eliminate ambiguities in quantum corrections to the two-dimensional kink, to the case of spinning strings moving in AdS4×CP3, thought of as another kind of two-dimensional soliton. We find that this eliminates the ambiguities and selects the result compatible with AdS/CFT, providing a solid foundation for one of the previous calculations, which found agreement. The method can be applied to other classical string «solitons.» © 2013 World Scientific Publishing Company.
Keywords: quantum corrections to solitons; String solutions; the AdS/CFT correspondence